Analysis of The Delay in The Implementation of Toll Road Project Work - Jati Irawan (Green Publisher Indonesia, 2025)
Infrastructure development is crucial for economic progress, and Indonesia has witnessed significant advancements in this sector, especially in toll road projects over the past decade. The Indonesian government, through the Ministry of Public Works and Housing (PUPR), is dedicated to infrastructure development to achieve the